Deretroflexion and alveolarization in quechua words (II) - Abanto Valverde, Jonathan (2015)
The relationship between Quechua phonemes /ĉ/ and /t/, unlike Aymara, has barely if ever been examined. Although it is a low-frequency phenomenon, it is possible that /č/, /t/ even /r/ in some Quechua words may go back to protophoneme */ĉ/. This study aims to corroborate the */ĉ/ > /t/ hypothesis by taking into account the alternation/change relationship between /č/ and /t/ phonemes.